Does Culture Matter? - Raquel Fernández (Institute for the Study of Labor (IZA), 2010)
This paper reviews the literature on culture and economics, focusing primarily on the epidemiological approach. The epidemiological approach studies the variation in outcomes across different immigrant groups residing in the same country. Immigrants presumably differ in their cultures but share a common institutional and economic environment. This allows one to separate the effect of culture from the original economic and institutional environment. This approach has been used to study a variety of issues, including female labor force participation, fertility, labor market regulation, redistribution, growth, and financial development among others.
urn:nbn:de:101:1-201010132778
Keywords: O10; Z1; D01; D1; 330; culture; beliefs; preferences; norms